Unveiling trends and gaps: A systematic review of business English teaching research in China (2007–2023) - Ke Hu; Asmaa AlSaqqaf (Castledown Group Pty Ltd, 2025)
A rapidly increasing body of research shows that language skills significantly impact decision-making in today’s globalized business environments. Based on findings from a large data-driven literature sur- vey using the PRISMA framework, this study applied descriptive statistics and content analysis to pro- vide a comprehensive synthesis of key features of China’s business English teaching, as seen through the lens of n = 23 major research studies, drawn from a total of N = 521 English journal articles published during 2007 to 2023. The synthesis suggests that (1) curriculum development, language acquisition, technology-aided language learning, and assessment in language learning were found to be the most focal topics among business English teaching; and (2) in most studies, quantitative research was utilized compared to a medium use of mixed methods and the least use of a qualitative approach to address issues raised within business English teaching. However, (3) a clear gap is identified by con- sidering these findings for future research agendas, suggesting a possible investigation into teaching reforms of business English teaching and research methodology and setting. This study also advocates for more multi-level studies and suggests paying greater attention to potential new data sources and means of analysis. Future directions and implications are also discussed.